Early experiences with quality-assured HbA1c and professional glucose point-of-care testing in general practice: a cross-sectional observational study among patients, nurses and doctors - Marleen Smits; Rogier Hopstaken; Lusan Terhaag; Gijs de Kort; Paul Giesen (BMC, 2022)
Abstract Background Point-of-care testing (POCT) is increasingly used in primary care. The rapid availability of the test result during the patient encounter increases the potential for patients and care providers to make a direct and joint decision on disease management. Our aim was to get insight into the first experiences of patients and healthcare professionals after introducing quality-controlled HbA1c and professional glucose POCT in diabetes care in their own general practices. Methods A cross-sectional observational study using paper questionnaires for patients, nurses and general practitioners (GPs) in 13 general practices in the Netherlands. HbA1c and professional glucose POCT was introduced after training and under day-to-day quality control. Patients filled in the questionnaire immediately after the test; nurses and GPs after a minimum period of three months from the starting date. Descriptive data analyses were performed. Results A total of 1551 fingerstick blood POC tests were performed (1126 HbA1c; 425 Glucose). For HbA1c POCT, 84 patients, 29 nurses and 11 GPs filled in the questionnaires. For professional glucose POCT, 30 patients, 17 nurses and 8 GPs responded. Response rates varied between 24 and 56%. Patients, nurses and GPs were generally (very) satisfied with the novel POC tests. Patients were most positive about the location (in the GPs' office) and execution of the POC test (by their own nurse), and the speed of the test result. Almost all nurses indicated to have sufficient knowledge and skills to perform the test. Both nurses and GPs had confidence in the test results and indicated they experienced a higher patient satisfaction than with regular blood tests. Perceived disadvantages were the time required to regularly calibrate the devices and the extension of the consultation time because of the test. Patients, nurses and GPs generally expressed they wanted to continue performing these POC tests in routine diabetes care. Conclusions Patients, nurses and GPs expressed (very) positive first experiences after introducing HbA1c and professional glucose testing on two high-quality POCT devices in their own general practices. Further research, with a random selection procedure of practices and patients and in other regions and countries, is recommended to confirm these findings.